Pelatihan Kewirausahaan dan Manajemen Pengelolaan Kelompok Tani Berbasis UKM Pada Kelompok Tani di Desa Curio - Rista Astari Rusdin; Ekajayanti Kining; Baharuddin Baharuddin; Wilda Widiawati; Suharman Suharman; Ilham Assidiq; Dian Firdiani; Idham Khaliq; Elihami Elihami (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
This community service aims to provide knowledge and skills to farmer groups through entrepreneurship training and management of SME-based farmer groups. The method used is training with the farmer group Tunas Muda Kreatif in Curio Village, Enrekang Regency. The results of this service activity are increased motivation and knowledge of farmer groups to develop their farmer groups, more optimal function of farmer groups as a forum for farmers to realize an increase in SME-based farming.